Pengaruh Medication Therapy Management (MTM) terhadap Tingkat Pengetahuan dan Kualitas Hidup Pasien Diabetes Melitus Di Puskesmas Kota Yogyakarta - Nita Trinovitasari; Nanang Munif Yasin; Chairun Wiedyaningsih (Jurnal Farmasi Indonesia, 2020)
The problem that often occurs in diabetes patients is the lack of knowledge related to treatment and illness. This problem can be overcome by providing education to patients collaboratively and continuously. One intervention that can be done is the Medication Therapy Management (MTM) service. MTM is a service that aims to optimize patient therapy outcomes. This recently implemented service has quite a several elements. So, this study modifies MTM service referenced from the MTM BPJS (Social Security Administering Body). This study aims to determine the effect of MTM services to the level of knowledge and quality of life on diabetes mellitus patients in Yogyakarta Public Health Center. The employed research method was quasi-experimental one-group design with pretest-posttest design and experiments were conducted in March to April 2020. The sampling method uses a purposive sampling technique. This study uses a questionnaire as a research instrument. Data were analyzed using SPSS. Results show a slight increase in the patients’ knowledge from 8.9 ± 2.3 to 11.6 ± 1.5 after MTM services were given with p-value of 0.000, and a slight increase in the quality of life of patients from 50.56 ± 3.9 to 52.84 ± 4.3 with a p-value of 0.003. In conclusion, the MTM-based services from pharmacists can significantly increase the knowledge and quality of life of diabetic patients.